HUBUNGAN ANTARA USIA DAN INDEKS MASSA TUBUH (IMT) DENGAN KEJADIAN OSTEOARTHRITIS LUTUT PADA PEREMPUAN DI RUMAH SAKIT SANTA ELISABETH LUBUK BAJA KOTA BATAM PERIODE 2022 - Christina, Yani; Sudarsono, Sudarsono; Fatmawati, Nurul (Universitas Batam, 2024)
Background: Knee osteoarthritis is a multifactorial degenerative joint disease associated with damage to the cartilage of the knee joint. Risk factors that play a role are increasing age, body mass index. OA affects ³ 45 years of age. This study aims to determine the relationship between age and body mass index with the incidence of knee osteoarthritis in women at Santa Elisabeth Hospital Lubuk Baja Batam City. Methods: This research is a type of quantitative research. This research method is analytic observation with a cross sectional approach conducted at Santa Elisabeth Hospital Lubuk Baja Batam City for the period 2022. Data were taken from medical records. The sampling technique was purposive sampling with a total sample size of 62 patients. The results of the study were analyzed by frequency distribution and then tested with the Chi-Square correlation test to determine the relationship. Results: The results showed the relationship between knee osteoarthritis with age p = 0.000 (significant), the relationship between knee osteoarthritis with body mass index p = 0.000 (significant). Conclusion: Based on the results of the study, it was concluded that there was a significant relationship between age and body mass index with the incidence of knee osteoarthritis in women at Santa Elisabeth Hospital Lubuk Baja Batam City.